Emerging mechanisms of aminoacyl-tRNA synthetase mutations in recessive and dominant human disease - Meyer-Schuman, Rebecca (Hum Mol Genet, 2017)
Aminoacyl-tRNA synthetases (ARSs) are responsible for charging amino acids to cognate tRNA molecules, which is the essential first step of protein translation. Interestingly, mutations in genes encoding ARS enzymes have been implicated in a broad spectrum of human inherited diseases. Bi-allelic mutations in ARSs typically cause severe, early-onset, recessive diseases that affect a wide range of tissues. The vast majority of these mutations show loss-of-function effects and impair protein translation. However, it is not clear how a subset cause tissue-specific phenotypes. In contrast, dominant ARS-mediated diseases specifically affect the peripheral nervous system—most commonly causing axonal peripheral neuropathy—and usually manifest later in life. These neuropathies are linked to heterozygosity for missense mutations in five ARS genes, which points to a shared mechanism of disease. However, it is not clear if a loss-of-function mechanism or a toxic gain-of-function mechanism is responsible for ARS-mediated neuropathy, or if a combination of these mechanisms operate on a mutation-specific basis. Here, we review our current understanding of recessive and dominant ARS-mediated disease. We also propose future directions for defining the molecular mechanisms of ARS mutations toward designing therapies for affected patient populations.